Draft Annual Plan 1989-90 Government of Punjab - Planning Commission (Planning Commission, 1989)
The Seventh Plan size for the Punjab State has been fixed at Rs. 3,285.00 crore. the expenditure during first three years of the Seventh Plan has been Rs. 1960.45 crore. the allocation for 1988-89 is Rs. 700 crore. the total expenditure till the end of the current year is estimated to be Rs. 2,660.45 crore, leaving a balance of Rs. 624.55 crore. Between 1986- 87 and 1988-89 the power outlay had to be substantially increased to provide adequate funds for the Dam, even though its commissioning was scheduled for the Eighth Plan, as well as for expeditious and timely completion of two major Power projects, namely, Ropar Thermal Project Stage-II and Mukerian Hydel Project.
Department of Planning Government of Punjab